2019
DOI: 10.1002/jcla.22831
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between serum amyloid A, C‐reactive protein and clinical indices of patients with acutely exacerbated chronic obstructive pulmonary disease

Abstract: BackgroundTo explore the correlations between SAA, CRP, and clinical indices of patients with acutely exacerbated chronic obstructive pulmonary disease (AECOPD).MethodsA total of 120 patients with AECOPD and another 120 with remitted COPD were enrolled in an AECOPD group and a COPD remission group, respectively. Meanwhile, 120 healthy subjects were included as a control group. SAA, CRP, PCT, Fbg, IL‐8, IL‐6, TNF‐α, and IP‐10 levels were detected. FEV1 and FEV1/FVC were measured.ResultsCompared with control gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 23 publications
2
15
0
Order By: Relevance
“…Serum amyloid A is an important acute-phase reactive protein mainly produced by liver, which can eliminate pathogens in the body and facilitate disease recovery. 18,19 And thus, it is a very sensitive marker reflecting an acute inflammatory state. 20 This study combined the regional characteristics of population distribution and eating habits in coastal cities, established strict normative inclusion and exclusion criteria for reference individuals, and finally confirmed 2365 healthy people with physical examinations as the research cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Serum amyloid A is an important acute-phase reactive protein mainly produced by liver, which can eliminate pathogens in the body and facilitate disease recovery. 18,19 And thus, it is a very sensitive marker reflecting an acute inflammatory state. 20 This study combined the regional characteristics of population distribution and eating habits in coastal cities, established strict normative inclusion and exclusion criteria for reference individuals, and finally confirmed 2365 healthy people with physical examinations as the research cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, serum levels of SAA and CRP together with other in ammatory markers (e.g. IL-6,IL-8, TNF-a, IP-10) were signi cantly greater in COPD patients experiencing an exacerbation than during remission and in healthy control subjects 24 .…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies showed that SAA is dramatically increased during acute phase of a COPD exacerbation, and that SAA is a sensitive biomarker for exacerbation severity in COPD patients 14 . Other studies showed increased circulating SAA concentration in COPD and other pulmonary diseases such as idiopathic pulmonary brosis (IPF) [22][23][24] . Formiga et al reported that inspiratory muscle performance was considerably lower in COPD patients with greater SAA concentration 23 .…”
Section: Discussionmentioning
confidence: 99%
“…14 Other studies showed increased circulating SAA concentration in COPD and other pulmonary diseases such as idiopathic pulmonary fibrosis (IPF). [22][23][24] Formiga et al reported that inspiratory muscle performance was considerably lower in COPD patients with greater SAA concentration. 23 In addition, SAA was greater in patients with IPF than in healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…22 Furthermore, serum levels of SAA and CRP together with other inflammatory markers (eg, IL-6, IL-8, TNF-a, IP-10) were significantly greater in COPD patients experiencing an exacerbation than during remission and in healthy control subjects. 24 Elevated SAA was reported in patients with cardiovascular disease where COPD was a comorbidity. 25 Since half of the deaths in COPD are associated with cardiovascular events, and the incidence of these events increases dramatically after each exacerbation, 26,27 and also because SAA is a good predictor of coronary artery disease as well as future cardiovascular events, SAA might be considered as a potential indicator of frequent exacerbation phenotype as well as an indicator of comorbid cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%